Language Preferences on Websites and in Google Searches for Human Health and Food Information - Singh, Punam Mony; Wight, Carly A; Sercinoglu, Olcan; Wilson, David C; Boytsov, Artem; Raizada, Manish N (JMIR Publications, 2007)
Background While it is known that the majority of pages on the World Wide Web are in English, little is known about the preferred language of users searching for health information online. Objectives (1) To help global and domestic publishers, for example health and food agencies, to determine the need for translation of online information from English into local languages. (2) To help these agencies determine which language(s) they should select when publishing information online in target nations and for target subpopulations within nations. Methods To estimate the percentage of Web publishers that translate their health and food websites, we measured the frequency at which domain names retrieved by Google overlap for language translations of the same health-related search term. To quantify language choice of searchers from different countries, Google provided estimates of the rate at which its search engine was queried in six languages relative to English for the terms "avian flu," "tuberculosis," "schizophrenia," and "maize" (corn) from January 2004 to April 2006. The estimate was based on a 20% sample of all Google queries from 227 nations. Results We estimate that 80%-90% of health- and food-related institutions do not translate their websites into multiple languages, even when the information concerns pandemic disease such as avian influenza. Although Internet users are often well-educated, there was a strong preference for searching for health and food information in the local language, rather than English. For "avian flu," we found that only 1% of searches in non-English-speaking nations were in English, whereas for "tuberculosis" or "schizophrenia," about 4%-40% of searches in non-English countries employed English. A subset of searches for health information presumably originating from immigrants occurred in their native tongue, not the language of the adopted country. However, Spanish-language online searches for "avian flu," "schizophrenia," and "maize/corn" in the United States occurred at only <1% of the English search rate, although the US online Hispanic population constitutes 12% of the total US online population. Sub-Saharan Africa and Bangladesh searches for health information occurred in unexpected languages, perhaps reflecting the presence of aid workers and the global migration of Internet users, respectively. In Latin America, indigenous-language search terms were often used rather than Spanish. Conclusions (1) Based on the strong preference for searching the Internet for health information in the local language, indigenous language, or immigrant language of origin, global and domestic health and food agencies should continue their efforts to translate their institutional websites into more languages. (2) We have provided linguistic online search pattern data to help health and food agencies better select languages for targeted website publishing.